Incorporação e uso de tecnologias digitais pelos professores no fazer pedagógico da educação básica - Martoni, Juliano (Universidade Federal de São Carlos, 2017)
In recent decades, the world has seen a series of economic, political and social transformations engendered by the presence of digital information and communication technologies (TDIC). In the midst of the changes, the school, an institution par excellence dedicated to the training of individuals, would not be oblivious to this process, so that, abruptly, digital technological devices started to enter it, spontaneously brought by the subjects that compose it or by enterprises based in a modernization logic. Concomitant to this, expectations emerged regarding a new teaching profile, capable of enjoying the maximum possibilities offered by TDIC. However, due to a series of circumstances, questions are raised as to the real conditions for teachers to incorporate technologies in their pedagogical practice. And if the answers are negative, there is a risk that digital technologies will become an obstacle to the pedagogical process.
Incorporation and use of digital technologies by teacher in pedagogical work of elementary schools
Keywords: TDIC; Trabalho docente; Educação híbrida; Formação docente; CIENCIAS HUMANAS::EDUCACAO::CURRICULO